2018
DOI: 10.1590/0103-8478cr20170449
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic methods for identification of root-knot nematodes species from Brazil

Abstract: The accurate identification of root-knot nematode (RKN) species (Meloidogyne spp.) is essential for implementing management strategies. Methods based on the morphology of adults, isozymes phenotypes and DNA analysis can be used for the diagnosis of RKN. Traditionally, RKN species are identified by the analysis of the perineal patterns and esterase phenotypes. For both procedures, mature females are required. Over the last few decades, accurate and rapid molecular techniques have been validated for RKN diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 35 publications
0
28
0
10
Order By: Relevance
“…In order to manage the root-knot nematodes, the ideal is to identify the species that are occurring in the area (CUNHA et al, 2018). In an area that only occurs M. enterolobii, for example, in addition to the cultivars resistant to the three species evaluated, we can recommend the planting of the cultivar Black Seed Simpson.…”
Section: Resultsmentioning
confidence: 99%
“…In order to manage the root-knot nematodes, the ideal is to identify the species that are occurring in the area (CUNHA et al, 2018). In an area that only occurs M. enterolobii, for example, in addition to the cultivars resistant to the three species evaluated, we can recommend the planting of the cultivar Black Seed Simpson.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that morphological and morphometrical methods for the identification species of RKNs are considerably time consuming and there is a lot of ambiguity, using species-specific primers could be a rapid method for detection (these primers listed in Cunha et al, 2018). The genetic diversity among M. javanica populations has been inferred by different markers (reviewed in Blok and Powers, 2009;Mokaram Hesar et al, 2011).…”
mentioning
confidence: 99%
“…The presence of the Mi gene confers resistance to M. incognita, M. javanica, M. arenaria and to insects such as aphids and whiteflies. Some species and/or populations of Meloidogyne called virulent pathotypes have the capacity to withstand high temperatures and supplant the resistance conferred by the Mi gene (CORTADA et al, 2011). In addition, expression of the Mi gene is heat sensitive and its effect can be lost when the soil temperature surpasses 28 °C, allowing the nematode to reproduce in the plant root, even if it contains the resistance gene (DROPKIN, 1969).…”
mentioning
confidence: 99%
“…Isoenzymatic of esterase (EST-I1) and malate dehydrogenase (MDH-N1) phenotypes showed patterns characteristic of M. incognita specie ( Figure 1C-D). However, for more refined phylogenetic studies a more complete diagnosis using molecular techniques is also suggested (CUNHA, et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation